Comparison of the Streptococcus mutans and Lactobacillus colony count changes in saliva following chlorhexidine (0.12%) mouth rinse, combination mouth rinse, and green tea extract (0.5%) mouth rinse in children - Rahul J Hegde; Shamika Kamath (Wolters Kluwer Medknow Publications, 2017)
Background: Compounds present in green tea have been shown to inhibit the growth and activity of bacteria associated with oral infections. The purpose of this study was to compare the efficacy of chlorhexidine (0.12%) mouth rinse and combination (chlorhexidine and sodium fluoride) mouth rinse to that of green tea extract (0.5%) mouth rinse in reducing the salivary count of Streptococcus mutans and Lactobacillus in children. Materials and Methods: The sample for the study consisted of 75 school children aged 8-12 years with four or more (decay component) of decayed, missing, and filled teeth index. Children were divided randomly into three equal groups and were asked to rinse with the prescribed mouth rinse once daily for 2 weeks after breakfast under supervision. Nonstimulated whole salivary sample (2 ml) was collected at baseline and postrinsing and tested for the colony forming units of S. mutans and Lactobacillus. Results: The results of the study indicate that there was a statistically significant reduction in S. mutans and lactobacilli count in all the three study groups. The statistically significant reduction in the mean S. mutans and lactobacilli counts were more in 0.12% chlorhexidine group than in the combination mouth rinse and 0.5% green tea mouth rinse group. There was no statistically significant difference in the reduction of S. mutans and lactobacilli count between combination mouth rinse group and 0.5% green tea mouth rinse group. Conclusion: Green tea mouth rinse can be a promising preventive therapy worldwide for the prevention of dental caries.